Comparison Of Long-term Trend Of Solar Radius With Sunspot Activity And Flare Index - Gölbaşı, Orhan; Kılıç, Hüseyin (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2011)
Results are presented from a study of solar radius measurements taken with the solar astrolabe at the TUBITAK National Observatory (TUG) over seven years, 2001-2007. The data series with standard deviation of 0.35 arcsec shows the long-term variational trend with 0.04 arcsec/year. On the other hand, the data series of solar radius are compared with the data of sunspot activity and H-alpha flare index for the same period. Over the seven year trend, we have found significant linear anti-correlations between the solar radius and other indicators such as sunspot numbers, sunspot areas, and H-alpha flare index. While the solar radius displays the strongest anti-correlation (-0.7676) with sunspot numbers, it shows a significant anti-correlation of -0.6365 with sunspot areas. But, the anti-correlation between the solar radius and H-alpha flare index is found to be -0.4975, slightly lower than others. In addition, we computed Hurst exponent of the data sets ranging between 0.7214 and 0.7996, exhibiting the persistent behavior for the long term trend. In the light of the strong correlations with high significance, we may suggest that there are a causal relationship between the solar radius and solar time series such as sunspot activity and H-alpha flare index.
Keywords: solar radius; oscillation; sunspot activity; flare index; calern-observatory astrolabe; diameter measurements; ccd astrolabe; cycle dependence; apparent radius; hurst analysis; disk sextant; sun; persistence; irradiance; güneş yarıçapı; salınım; güneş lekesi aktivitesi; parlama indeks; calern-gözlemevi usturlap; çap ölçümleri; ccd usturlap; döngüsü bağımlılığı; belirgin yarıçapı; hurst analizi; Disk sekstant; Güneş; sebat; parlama